Cognitive declines following bilateral subthalamic nucleus deep brain stimulation for the treatment of Parkinson's disease. Issue 7 (26th October 2007) - York, M K; Dulay, M; Macias, A; Levin, H S; Grossman, R; Simpson, R; Jankovic, J
Abstract : Background: We investigated the cognitive and psychiatric outcome 6 months after bilateral subthalamic nucleus deep brain stimulation (DBS) for the treatment of Parkinson's disease (PD) using a disease control group. Methods: 23 patients who underwent DBS were compared with 28 medically treated patients with PD at baseline and at 6 months for neuropsychological measures. In addition to the group outcomes, we report reliable change indices (RCI) and a dementia caseness analysis. Results: Patients who underwent DBS demonstrated a significant decline in verbal memory compared with the control group (p<0.003), and trends for decline on oral information processing, including verbal fluency, timed transcription and word naming. Patients who underwent DBS demonstrated declines in attention, set shifting and semantic fluency but these changes were similar to the rate of decline in the PD group. RCI indicated that patients who underwent DBS demonstrated clinically significant declines in verbal fluency (p<0.01) and inhibition of a dominant response (p<0.003), with trends for declines in set shifting (p<0.02) and verbal long term recall (p<0.08), indicative of frontostriatal dysfunction. Patients who underwent DBS did not demonstrate significant changes in depression, anxiety or psychological distress scores. The caseness analysis revealed that one of the patients who underwent DBS (4%) converted to dementia over 6 months compared with none of the PD controls. Conclusions: Our findings demonstrated that patients who underwent DBS experienced declines in verbal recall and trends for declines in oral information processing 6 months following surgery, even when good motor outcome was achieved. Potential candidates should be counselled about the risk of mild frontostriatal cognitive declines following DBS to weigh the risks and benefits of surgery.